ANALYSIS OF THE FIBER CONTENT OF DIETS SERVED FOR DIABETICS PATIENTS FROM A PUBLIC NETWORK HOSPITAL - Cristina Ramos Costa, Leandra; de Cássia Lucena Duarte, Rita; Pereira Pinto Dias, Luciana (Health and Society, 2023)
Introduction: Diabetes mellitus is a disease characterized by high blood clusters of glucose resulting from failure of insulin secretion. Purpose: To analyze the fiber content served to patients of a public network hospital. Materials and methods: Descriptive cross-sectional study conducted at the Hospital Dr. Carlos Macieira’s Food Unit from May to September, 2018. Daily, 3 hot flushes of each diet (liquid restricted, pasty liquid, pasty and soft / free) diabetics were weighed after cupping on a digital scale. For each preparation, 3 weighings were performed separately. The data were tabulated and analyzed in the Excel 2010® program. The variables were described in absolute and relative frequencies, presented by means of charts and graph. The analysis of the fiber content was done through the TACO Table, 2011 following the daily recommendations for diabetics of 25g of FAO / WHO. Results: It was observed that the meals with higher fiber content in the diets, liquid pasty was lunch (13.05g) and in the pastous and soft / free was dinner (5.22g) and (17.71g), respectively. On the other hand, the meals with lower fiber content in the diets, liquid pasty was the dinner (1.93g), pasty, the afternoon snack (1.38g) and the soft / free, the supper (1.20g). The total fibers found in the menu were: restricted liquid diet (0g), pasty liquid, (22.25g), pasty (17.36g) and free / soft (37.78g) fibers. Conclusion: The amount of fiber offered in the soft / free diet exceeded the recommendation, whereas in the pasty and pasty liquid diets it was lower than the daily recommendation for diabetics.